Challenging preconceptions of the European Iron Age : essays in honour of Professor John Collis - Morrison, Wendy A.,; Collis, John, 1944 May 19- (Archaeopress Archaeology, 2022)
This collection of essays by leading researchers in the archaeology of the European Iron Age pays tribute to Professor John Collis who, since the 1960s, has been involved in investigating and enriching our understanding of Iron Age society and, crucially, questioning the status quo of our narratives about the past.